An experimental study of arsenic and lead concentration in common food sources - Ghani, Abdul; Sahito, Ambreen; Naeem, Shahla; Kayama, Fujio; Fatmi, Zafar (International Journal Of Community Medicine And Public Health, 2018)
This study estimated the concentration of arsenic (As) and lead (Pb) in commonly used food items: chicken meat, potato and lentils. Furthermore, it also determined the contribution of As and Pb in food through leaching by different types of utensils. Samples of food were bought from open market of Karachi, Pakistan. Each food item was cooked under standardized condition for 20 minutes. The food samples were cooked in utensils made of four different types of materials which are commonly used for cooking. The As and Pb concentrations were determined by inductively coupled plasma mass spectrometry. None of the food items were free of As or Pb. Lentils cooked in aluminium and steel cookware had high concentration of Pb (55.1 and 34.6 ng/gm, respectively). The As concentration was higher in chicken meat (ranged from 41.3 to 47.7 ng/gm) compared to other food items. The chicken meat was uniformly contaminated with high As levels irrespective of the utensil material used for cooking. Thus, chicken meat could be potentially contaminated from external environment (mostly likely during raising). Aluminium or steel utensils have particular interaction with lentils and causes leaching of Pb during cooking. Exposure from As and Pb can be reduced by regulating food items and quality of cooking utensils.